ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA DI INDONESIA PERIODE 2008-2012 - Nadia Ayu AyuBhakti; Istiqomah Istiqomah; Suprapto Suprapto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2014)
Human Development Index (HDI) is an index established by UNDP in 1996 to measure the well-being of society. Indonesian HDI increased during the period of 2008-2012; however, there is high variation among 33 provinces. Its position in the world is still below the average (121 of 187 countries) and ranks 5th among ASEAN countries (UNDP, 2013). Based on this phenomenon this study tries to analyze the determinants of HDI which include GDP, dependency ratio, household consumption for food, government budget for education, and the budget for health. The results indicate that GDP and government budget for health have positive effect on HDI, whereas dependency ratio and household consumption for food have negative effect. However, the budget for education has no effect on HDI. HDI is an important indicator of development; therefore, the government and the society should take efforts to improve the HDI. Economic growth, income distribution, population control, poverty alleviation, as well as improvement in health services and education are needed in order to improve the HDI.